IS THE ECONOMIST TRAINED TO USE ACCOUNTING DATA? - Underwood, William (The Accounting Review, 1941)
Obviously it is impossible to approach every economist and ask him if he knows enough about accounting to use accounting material. Only about 20% of the economics departments of universities granting degrees in economics have any semester hour requirement in accounting. These requirements affected only 15% of the philosophy of doctorate graduated in the period. Where course hours in accounting are required, the work usually need not be of graduate character. The group that has had such training has probably not had enough to make full use of the available accounting data. While less than twenty per cent of the economics department members above the rank of instructor are prepared to teach accounting at the college level, about sixty per cent of heads of these departments feel that teachers of accounting should be so trained that they may be able to teach economics at college level. The distinction between accounting and economics is more apparent than real and forces are at work to bridge the gap between the two disciplines.